Comportamento, vacinação e direito à saúde: o uso de insights comportamentais como ferramenta complementar para o combate à redução vacinal infantil no Brasil - Santos, Luciana Rêgo dos (2022)
Vaccination has a history of success in global health and development, saving millions of lives every year. Currently, the growth of behavioral phenomena such as vaccine hesitancy has demanded from governments the need to deal with important ethical dilemmas related to mandatory vaccination. Nationally, low vaccine coverage rates are worrying, especially when it comes to vaccination for children. Since 2016, Brazil has faced a significant decrease in children vaccination, especially regarding the vaccines provided for in the national vaccination schedule for children up to five years old. In addition, the decrease in vaccination coverage in Brazil increased significantly during 2020 due to the Covid-19 pandemic. The search for high and homogeneous vaccine coverage in Brazil should be a priority, in order to achieve the implementation of basic precepts established by the Federal Constitution of 1988. This study has a descriptive nature, being developed through a qualitative approach, according to the deductive method, through bibliographic and documentary research with an interdisciplinary approach, aiming to analyze essentially whether Behavioral Economics can contribute to the effectiveness of the right to health, especially with regard to overcoming barriers (behavioral and non-behavioral) related to the reduction of childhood vaccination coverage in Brazil. At the end, the research concluded that traditional policies, such as legislation, incentives and information, are not being enough to achieve high rates of homogeneity and childhood vaccination coverage in the national scenario, beside identifying the incidence of several behavioral barriers. Thus, it was found that Behavioral Economics can contribute to the effectiveness of the right to health, especially with regard to overcoming behavioral barriers related to the reduction of childhood vaccination coverage in Brazil. In addition, it was also verified that the information barriers found may also benefit from the support of behavioral elements to overcome them. Finally, new strategies and behavioral solutions may and shall be used to complement traditionally elected public vaccination policies, in order to strengthen and garantee the right to health in the national scenario.